A gestão da informação como auxílio a tomada de decisão em uma unidade acadêmica pública federal de ensino superior: um estudo de caso - Sousa Neto, Vicente Daniel de (2018)
Information is an institutional element that properly studied can become a strategic resource for any organization, including public management. Within the university public environment, in addition to the higher bodies, the academic units need new tools that subsidize the various decision-making of their management. This research deals with the study of information management as support for decision making in an academic environment of a federal institution of higher education, FACE / UFG. Its general objective is to develop an effective tool for information management as a way to contribute to the decision making process of academic unit management. Specifically, it is intended to apply the proposed instrument, to recognize and represent the information needs within the teaching, research and extension triad, to analyze the effectiveness of the instrument and to prepare a recommendation plan for FACE / UFG. The research was characterized as exploratory, of an applied nature and case study, through a qualitative-quantitative approach. The orientation of the research was based on the phases of the proposed instrument, based on the adaptation of the information management model of Choo (2006) and the Reference Morphology of Albuquerque (2012). As a result, it was possible to diagnose the academic environment, to recognize their information needs, as well as to represent them in a way that contributes to the development of a database of a Management Information System. In this way the present study reached the proposed objectives, cooperating, consequently, socially and technologically with the public administration.